Risk of Impingement on Polyethylene Liner of Total Hip Arthroplasty Prosthesis during Muslim Prayer (Salat) Activity - Anwar, Iwan Budiwan; Saputra, Eko; Ismail, Rifky; Jamari, J.; Van der Heide, Emile (Open Access Macedonian Journal of Medical Sciences, 2020)
Total hip arthroplasty (THA) is one of the most successful orthopedic surgical procedures. Impingement believed to be the most common mechanism of dislocation after THA. Salat consist of several repeated physical movements which require several extreme hip joint movements. The potential impingement positions during salat activity have been revealed by the previous computer simulation study, some evidences of impingement from retrieved polyethylene liner also have been revealed from our recent preliminary data. Although further study is still needed in this field, we may give special advice to modify some movement for Muslim patient who receive THA when performing Salat activity.